Rankings in the Age of Surveillance Capitalism - Hazelkorn, Ellen (International Higher Education, 2025)
<h3 id="university-rankings-are-now-a-global-phenomenon-having-begun-as-a-transparency-and-accountability-instrument-they-have-morphed-into-an-indicator-of-global-competitiveness-for-knowledge-and-talent-and-have-been-transformed-from-an-information-tool-into-a-complex-global-intelligence-business-in-our-current-data-driven-age-the-concepts-of-monopolies-of-knowledge-information-asymmetry-and-surveillance-capitalism-can-help-us-better-understand-how-the-fusion-of-data-and-capitalism-are-influencing-and-shaping-the-future-of-higher-education-policy-practice-and-research" data-pm-slice="1 1 []">University rankings are now a global phenomenon. Having begun as a transparency and accountability instrument, they have morphed into an indicator of global competitiveness for knowledge and talent and have been transformed from an information tool into a complex global intelligence business. In our current data-driven age, the concepts of “monopolies of knowledge,” “information asymmetry,” and “surveillance capitalism” can help us better understand how the fusion of data and capitalism are influencing and shaping the future of higher education policy, practice, and research.